2010
DOI: 10.5194/hessd-7-5805-2010
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rain event properties and dimensionless rain event hyetographs at the source of the Blue Nile River

Abstract: In the present study, the spatial and temporal patterns of the rain event properties are analysed. The event properties are rain event depth, event duration, mean event intensity, peak intensity and the time span between two consecutive rain events which is referred to as inter-event time (IET). Dimensionless event hyetographs are established by relating fractions of event intensities to the corresponding fractions of event durations. The spatial variation of the characteristics of the hyetographs is also eval… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…To separate rainfall events, a guideline value for the minimum dry period length between two wet periods has to be set. Such a guideline is known as the minimum inter‐event time (MIT) (Dunkerley, ; Haile et al ., , ) or inter‐event time definition (IETD) (Palynchuk and Guo, ; Balistrocchi and Bacchi, ). If the dry period between two wet periods is equal to or longer than the minimum inter‐event time, they are considered to be two separate rainfall events; if the dry period is shorter than the minimum inter‐event time, they are considered to be a single rainfall event.…”
Section: Methodsmentioning
confidence: 99%
“…To separate rainfall events, a guideline value for the minimum dry period length between two wet periods has to be set. Such a guideline is known as the minimum inter‐event time (MIT) (Dunkerley, ; Haile et al ., , ) or inter‐event time definition (IETD) (Palynchuk and Guo, ; Balistrocchi and Bacchi, ). If the dry period between two wet periods is equal to or longer than the minimum inter‐event time, they are considered to be two separate rainfall events; if the dry period is shorter than the minimum inter‐event time, they are considered to be a single rainfall event.…”
Section: Methodsmentioning
confidence: 99%
“…One of the most widely used criteria for the separation of rainfall events is minimum inter‐event time (MIT) (Heneker et al, ; Haile et al, ; ), which is also known as inter‐event time definition (IETD) (Guo and Baetz, ; Branham and Behera, ; Balistrocchi and Bacchi, ). The dry period between two wet periods is known as inter‐event time, and if it is equal to or longer than the desired MIT or IETD, they are considered as two individual events.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to (ii), Haile et al (2009a) showed that both Sekela and Jema have large seasonal rainfall but Jema receives more frequent and high intensity rain events while Sekela receives clustered hourly rainfall with mostly light to moderate rainfall intensities. Haile et al (2009c) showed that rainfall ii the lowland areas of Gilgel Abbay can be characterized by large depth, high intensity, short duration and long inter-event time as compared to the mountain areas. As a result of the differences in rainfall properties, removing Jema and Sekela from the network can result in larger differences in the estimated spatial rainfall as compared to removing any of the other stations.…”
Section: Nsementioning
confidence: 99%